2010 International Electron Devices Meeting 2010
DOI: 10.1109/iedm.2010.5703310
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between channel mobility improvements and negative V<inf>th</inf> shifts in III&#x2013;V MISFETs: Dipole fluctuation as new scattering mechanism

Abstract: Channel mobility μ eff for InGaAs MISFETs is improved by using the (111)A surface orientation and (NH 4 ) 2 S treatment. These μ eff improvements are associated with negative shifts in V th and V fb . We propose that carrier scattering by fluctuated dipoles at the MIS interfaces contributes to μ eff for the III-V MISFETs. For the InP MISFETs, the effects of the interface dipoles are not apparent due to their inferior interface quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 7 publications
5
22
0
Order By: Relevance
“…We have also confirmed that the combination of InGaAs and ALD Al 2 O 3 can lead to superior MOS interface properties [64], often attributed to the cleaning effect of TMA on InGaAs surfaces [41][42][43]. Also, it has been reported that sulfur (S) passivation [65,66] and surface nitridation [67,68] can improve the Al 2 O 3 /InGaAs MOS interface properties. However, one of the drawback of Al 2 O 3 is the low dielectric constant (~ 9), which is not enough to provide low EOT gate stacks with low gate leakage current.…”
Section: Iii-v Gate Stack Technologiessupporting
confidence: 78%
“…We have also confirmed that the combination of InGaAs and ALD Al 2 O 3 can lead to superior MOS interface properties [64], often attributed to the cleaning effect of TMA on InGaAs surfaces [41][42][43]. Also, it has been reported that sulfur (S) passivation [65,66] and surface nitridation [67,68] can improve the Al 2 O 3 /InGaAs MOS interface properties. However, one of the drawback of Al 2 O 3 is the low dielectric constant (~ 9), which is not enough to provide low EOT gate stacks with low gate leakage current.…”
Section: Iii-v Gate Stack Technologiessupporting
confidence: 78%
“…Improvement of the MIS interface is a central issue in order for III-V channels to be successfully implemented in future CMOS circuits. It is widely recognized that native oxides on III-V surfaces deteriorate the MIS interface properties [1,2], and many interface control methods have been proposed to remove or modify these oxides, such as surface passivation by wet oxide etching [3,4], sulfur passivation [5,6], plasma cleaning [7,8], nitridation [9,10], Si deposition [11,12], and atomic layer deposition (ALD) using reducing reactants [13,14]. Among these studies, the effects of Al 2 O 3 ALD on III-V surfaces have been investigated extensively [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…It has already been reported that (111)A GaAs MOSFETs can also provide the higher mobility that (100) GaAs MOSFETs [70] and that the (111)A surfaces can significantly modulate the MOS interface structure and the electrical properties [71]. We have demonstrated that (111)A-surface InGaAs MOSFETs with TaN/Al 2 O 3 gate stacks can provide much higher mobility than the (100) one [68,72]. Here, the pre-gate treatment of the InGaAs surfaces was carried out by etching in a diluted HCl solution followed by immersion in an (NH 4 ) 2 S solution.…”
Section: N-gamentioning
confidence: 79%
“…It is found that the high enhancement factor of 2.2x against the Si mobility is obtained in high E eff region. While this mobility improvement might be attributable partly to the reduction in scattering due to surface dipole fluctuation [68], further experimental and theoretical studies are needed to identify the physical mechanism of the surface orientation dependence. However, these experimental findings strongly suggest that the surface orientation engineering is quite effective in III-V MOSFET as well.…”
Section: N-gamentioning
confidence: 99%